Classified metabolic power-based measures in professional football players: comparison between playing positions and match period - Akyildiz, Zeki; Cene, Erhan; Parim, Coskun; Cetin, Onat; Turan, Cagatay; Yuksel, Yilmaz; Silva, Rui; Silva, Ana Filipa; Nobari, Hadi (BMC, 2022)
Objective The aim of this study was (i) provide reference data of metabolic power-based measures during professional football matches; and to (ii) analyze the between-position and between-halves differences of power-based measures during professional football matches. Methods Forty-six professional male players from two Turkish Super League teams were observed during two seasons, and 58 matches were analyzed. Total distance, equivalent distance, Low Power (LP), Intermediate Power (IP), High Power (HP), Elevated Power (EP), Max Power (MP) and power metabolic measures P-met at different match moments were considered. Results Significant between-position differences were observed for IP (p: 0.000; d: 0.284), HP (p <= 0.001; d = 0.45), EP (p <= 0.001; d = 0.44), and for MP (p <= 0.001; d = 0.56), with the central defenders (CD) showing the lower values, and the central midfielders (CM) showing the higher values for the overall measures. Conclusion Power-based measures are dependent on playing positions. While the CD have lower P-met values when compared to all positions, the CM have the greatest values. Training and recovery strategies must be ensured for CM players, especially those who have greater match participation.
Keywords: Football; Metabolic power output; Positional differences; Match halves; ELITE SOCCER PLAYERS; TEAM SPORTS; ENERGY-COST; ACCELERATION; Rehabilitation; Sport Sciences